Analisis Rekonfigurasi Jaringan Menggunakan Particle Swarm Optimization untuk Meningkatkan Voltage Stability Index - Simamora, Yoakim; Astrid, Erita; Immanuel, Michael Fritz; Waluyo, Bakti Dwi; Sembiring, Muhammad Aulia Rahman; Dewy, Mega Silfia; Silitonga, Agnes Irene; Ginting, Lisa Melvi (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2025)
The distribution system is a part of the power system that distributes electrical energy from the transmission network to medium and low voltage consumers, such as households, industrial consumers, and other facilities. Network reconfiguration is the process of restructuring and configuring the network by opening and closing switches to obtain the most optimal network configuration. In this study, the determination of switch opening and closing uses the binary particle swarm optimization (BPSO) algorithm, whose basic principle in finding optimal values is based on the social behavior of birds flocking or fish swimming together.. To measure voltage stability, this research presents the Voltage Stability Index (VSI), improving voltage stability using network reconfiguration with the BPSO algorithm. In this study, the VSI value will be compared with other algorithms, including the PSO algorithm from previous research, the Cuckoo Search Algorithm (CSA), the Harmony Search Algorithm (HSA), and the Modified Whale Optimization Algorithm (MWOA). The simulation results show that the BPSO algorithm can reduce power loss from an initial value of 202.7 kW to 139.3 kW, a decrease of 31.28%. Compared to other algorithms, BPSO has the best percentage reduction in power loss. The simulation results also show that the VSI value improved from an initial value of 0.2112 to 0.1520, an increase of 28%. In improving the VSI value in the IEEE 33 bus distribution system, the BPSO algorithm became the best algorithm for enhancing the VSI value.